CMOS IC layout concepts, methodologies, and tools - Clein, Dan, 1958- (Boston : Newnes, 2000)
This book includes basic methodologies, review of basic electrical rules and how they apply, design rules, IC planning, detailed checklists for design review, specific layout design flows, specialized block design, interconnect design, and also additional information on design limitations due to production requirements. *Practical, hands-on approach to CMOS layout theory and design *Offers engineers and technicians the training materials they need to stay current in circuit design technology. *Covers manufacturing processes and their effect on layout and design decisions.
Introduction; Background; Layout Design; Specific Layout Design Flows; Advanced Techniques for specialized building block layout design; Advanced techniques for Building Block Interconnect Layout Design; Layout Design techniques to address Electrical characteristics; Layout considerations due to process requirements; Layout design techniques in an uncertain environment; Layout CAD Tools.
Includes index.
Keywords: Metal oxide semiconductors, Complementary -- Computer-aided design; Integrated circuits -- Computer-aided design; Integrated circuits; Metal oxide semiconductors, Complementary; Electronic books